PENGARUH PENURUNAN TARIF PAJAK UMKM DAN SISTEM PELAYANAN ONLINE TERHADAP PERSEPSI WAJIB PAJAK (STUDI KASUS PADA UMKM YANG TERDAFTAR DI KPP SEMARANG BARAT) - Nadhor, Khaerun; Fatoni, Nur; Nurudin, Nurudin; Zakiy, Faris Shalahuddin (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
Taxes are the largest source of state revenue, which is around 70%, so the government tries to increase tax revenues as much as possible by making policies that can later attract people to pay taxes. One of the government's policies is to reduce the final tax rate for public entrepreneurs, which is expected to make public entrepreneurs obedient to pay taxes. And take advantage of technological developments by conducting online tax services both in registration, reporting and tax payment. This study aims to determine the effect of decreasing MSME tax rates and online service systems on taxpayers 'perceptions of MSME taxpayers' compliance that are registered at the West Semarang KPP either partially or simultaneously. This research is quantitative research. The study population is a UMKM taxpayer registered at the West Semarang KPP. The sample was selected using the probability sampling method, which determines a random sample by taking 98 respondents as samples in this study. Data collection method is by field study. Test the feasibility of data on data taken using the validity and reliability test. Hypothesis testing uses multiple linear regression models, so it needs to be held a classic assumption test on the research data obtained. The results of the multiple linear regression test for the variable reduction in MSME tax rates and online service systems have a significant effect on taxpayers' perceptions of MSME taxpayer compliance, both simultaneously and partially.Â